The Law Enforcement in Implementation of Diversion on Children in Confrontation with the Law - Nur Khasanah; Umar Ma'ruf (Law Development Journal, 2020)
This study aims to analyze law enforcement in the application of diversion to children in conflict with the law. Constraints faced in applying diversion to children who are faced with the law and its solutions. This study uses a sociological juridical approach, with descriptive analytical research specifications. The data used in this study are secondary data obtained through library research and primary data which are then analyzed qualitatively using law enforcement theory and restorative justice theory. The result of this research is the action of transferring the settlement of juvenile cases from the criminal justice process to the non-criminal justice process. This diversion really needs child-specific handling that aims to provide the best interests of the child supported by adequate police human resources and the availability of legal assistance, community counselors, professional social workers and family / guardian and community support. Constraints faced a) Unifying Thoughts between Victims and Children in Conflict with the Law in order to Achieve an Agreement, b) Inadequate facilities and facilities, c) Community understanding of diversion is still lacking, d) Understanding of the community and other law enforcement officials on Diversion still lacking, e) The role of the community is still minimal, especially from the community who are victims, f) Cooperation with other agencies related to the implementation of Diversion has not been going well. Solutions to overcome these obstacles are a) Conducting separate meetings (caucuses) to unify ideas between victims and children in conflict with the law so that an agreement is reached, b) Optimizing facilities and infrastructure, c) Establishing Intensive Communication with Other Law Enforcement Officials. , d) Conducting Diversion Socialization among the Community, e) Making an Agreement on Supervision of the Implementation of the Diversion Agreement Results.